2002
DOI: 10.1107/s0907444901021266
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization and preliminary X-ray diffraction analysis ofL-aminoacylase from the hyperthermophilic archaeonThermococcus litoralis

Abstract: The enzyme l-aminoacylase catalyses the hydrolysis of N-acyll-amino acids from peptides or proteins. The recombinant enzyme from the hyperthermophilic archaeon Thermococcus litoralis has been puri®ed to homogeneity. This zinc-containing enzyme has been crystallized from ammonium sulfate using the sitting-drop vapourdiffusion method. The crystals diffract to 2.8 A Ê resolution and belong to the rhombohedral space group R32, with unit-cell parameters a = b = 102.4, c = 178.5 A Ê , = 120 in a hexagonal lattice se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The L-aminoacylase has been cloned and overexpressed in high yields from E. coli. This has enabled its biochemical characterization and crystallization [6,7]. The recombinant enzyme is thermostable, with a half-life of 25 h at 70 • C and can be immobilized and packed into a column reactor which can be used to convert substrate into product continuously for up to 10 days at 60 • C with no loss in activity of the enzyme [8].…”
Section: Aminoacylasementioning
confidence: 99%
“…The L-aminoacylase has been cloned and overexpressed in high yields from E. coli. This has enabled its biochemical characterization and crystallization [6,7]. The recombinant enzyme is thermostable, with a half-life of 25 h at 70 • C and can be immobilized and packed into a column reactor which can be used to convert substrate into product continuously for up to 10 days at 60 • C with no loss in activity of the enzyme [8].…”
Section: Aminoacylasementioning
confidence: 99%
“…These ions have been reported to inhibit the proteolytic activities of elastase strain K (Rahman et al, 2011), ME-4 (Cheng et al, 2009) and PseA (Gupta et al, 2005) which also happened to be metalloproteases. The highest half-life of aminoacylase was reported by Hollingsworth (2002), who found that the stability of aminoacylase from Thermococcus litoralis was 25 h at 70°C. Aminoacylase SZN can withstand a broad range of inhibitors and did not exhibit significant effects on its stability in detergent especially Tween 20.…”
Section: Discussionmentioning
confidence: 94%